Method for the preparation of hybrid polymer nanoparticles for the release of oligonucleotide drugs in regenerative, therapeutic and preventive pharmacological therapy

Hybrid polymer nanoparticles address the challenges of nucleic acid drug delivery by encapsulating oligonucleotides and hydrophobic drugs, ensuring high encapsulation efficiency and controlled release, enhancing biocompatibility and versatility for precision medicine.

JP2025501593APending Publication Date: 2025-01-22POLITECNICO DI TORINO +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024538063
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-23
Filing Date
2022-12-22
Publication Date
2025-01-22

AI Technical Summary

Technical Problem

Nucleic acid-based drugs face challenges such as degradation by nucleases, poor cellular uptake due to negative charge, and inefficient intracellular release, leading to instability and toxicity in existing nanotechnologies.

Method used

Hybrid polymer nanoparticles composed of a polymer component encapsulating cationic liposomes and/or lipoplexes, prepared via nanoprecipitation, which efficiently encapsulate oligonucleotides and hydrophobic drugs, allowing controlled and sustained release with biocompatible and versatile surface functionalization.

Benefits of technology

The nanoparticles provide high encapsulation efficiency (96-100%), stability for weeks, and controlled release of oligonucleotides, reducing systemic toxicity and enabling precision medicine applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501593000006
    Figure 2025501593000006
  • Figure 2025501593000007
    Figure 2025501593000007
  • Figure 2025501593000008
    Figure 2025501593000008
Patent Text Reader

Abstract

The present invention describes hybrid nanoparticles consisting of a polymer component encapsulating cationic liposomes and / or lipoplexes comprising cationic lipids and helper lipids, the polymer component comprising at least 80% by weight of the total material constituting the nanoparticle.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is directed to hybrid nanoparticles consisting of a polymer component encapsulating cationic liposomes and / or lipoplexes comprising cationic lipids and helper lipids. [Background technology]

[0002] Nucleic acid-based drugs are difficult to administer for the following reasons: a) They are easily degraded by nuclease-catalyzed hydrolysis on contact with biological fluids; b) when released locally or when they reach the desired site, they do not accumulate in the target tissue because their negative charge prevents the internalization of the oligonucleotide drug by cells; c) Unlike typical "small molecule" based drugs that can be easily delivered to target tissues, nucleic acid based drugs require efficient intracellular release.

[0003] To solve the problem of oligonucleotide drug release, various nanotechnologies have been proposed, including: (i) lipid nanoparticles, (ii) polymeric nanoparticles, (iii) inorganic nanoparticles, (iv) nanoneedle-based technology, and (v) viral vectors.

[0004] Lipid nanoparticles applied for the release of oligonucleotides (eg, miRNA, siRNA, mRNA) combine different types of lipids to obtain desired properties.

[0005] For example, cationic lipids are widely used at physiological pH because they can effectively complex oligonucleotide drugs. However, they often cause toxicity to cells. Cationic lipid nanoparticles have also been produced that can encapsulate oligonucleotide drugs and other drugs such as doxorubicin (Sci.Rep.,2016,6,https: / / doi.org / 10.1038 / SREP35223) and paclitaxel (Cancer Med.,2017,Vol.6,651-661). US10555910 describes lipid nanoparticles specific for mRNA inhibitors.

[0006] However, the main drawback is the cytotoxicity of cationic lipids and the high instability of the particles due to non-specific interactions with serum proteins, which are associated with activation of the immune system, including activation of the complement and coagulation pathways and stimulation of cytokine production.

[0007] This limitation was overcome by the introduction of neutral lipid particles based on ionizable lipids. These particles are positively charged only at a slightly acidic pH (allowing complexation with RNA), while being neutral at physiological pH, making them more biocompatible. Generally, lipids with amino moieties with an acid dissociation constant (pKa) of about 6.5 are used. Nanoparticles are obtained by rapidly mixing a lipid solution in ethanol and an aqueous solution of the oligonucleotide drug in water at low pH (pH 4), which may partially degrade the encapsulated drug. The nanoparticles thus produced have a low surface charge in physiological conditions and are non-cytotoxic and non-immunogenic. In general, lipid nanoparticles based on ionizable lipids at low pH also contain (i) helper lipids (allowing better liposome formation and facilitating interaction with cell membranes), (ii) cholesterol (which, due to its auxiliary function, allows better integration of the different lipid components), and (iii) pegylated lipids (limiting opsonization and reticuloendothelial clearance by serum proteins). However, a drawback is that the presence of a polyethylene glycol (PEG) coating can limit interaction with and release into target cells. This problem can be overcome by using pegylated lipids with a short acyl chain C14, which are rapidly released in vivo (Pharmaceutics, 2019, Vol. 11, https: / / doi.org / 10.3390 / PHARMACEUTICS11080360).

[0008] The relative composition of ionizable lipids, helper lipids, cholesterol, and pegylated lipids influences the efficacy of lipid nanoparticles and must be optimized for each application and method of administration. Furthermore, the type, size, and surface charge of the selected lipids are very important as they affect the in vivo behavior of lipid nanoparticles.

[0009] In particular, over 300 ionizable lipids were designed, synthesized, and structure-activity relationships were identified (Nat. Nanotechnol., 2019, Vol. 14, No. 12, 1084-1087). Particle activity was related to the acid dissociation constant of the cationic ionizable lipid, with an optimal pKa of ≒ 6.4. Deviations of even 0.5 units from this pKa reduced efficacy by up to 100-fold.

[0010] In 2018, the US Food and Drug Administration (FDA) and the European Commission (EC) approved patisiran (ALN-TTR02), a type of lipid nanoparticle (ionizable at low pH) for releasing short interfering RNA (siRNA), for the treatment of polyneuropathy induced by hereditary amyloidosis.

[0011] The latest examples of lipid nanoparticles releasing RNA molecules are represented by the Covid-19 BioNTech / Pfizer and Moderna vaccines, which release specific ribonucleic acid (mRNA).

[0012] However, the use of lipid nanoparticles is limited by poor storage stability due to instability in biological environments / aqueous solutions, thus necessitating freezing or the use of stabilizing agents (e.g., sucrose).

[0013] Another limitation of lipid particles is the non-specific release or systemic accumulation of oligonucleotide drugs.To surface-functionalize particles to ensure targeting action, it is preferable to use lipid agents that are pre-modified with ligands for cell targeting.This is to avoid post-preparation functionalization, which may be important due to the low stability of lipid particles.Therefore, the preparation process must be optimized for each surface functionalization, which limits versatility.

[0014] Cationic polymer nanoparticles for the release of oligonucleotide drugs have been proposed, and poly(ethyleneimine) (PEI) is often used. PEI-based particles with linear and branched polymer structures of low and high molecular weight can be obtained (Polyethyleneimines for siRNA and miRNA delivery in vivo, Wiley Interdiscip. Rev. Nanomed. Nanobiotechnol., 2013, Vol. 5, 484-501). The main drawbacks are cytotoxicity and low transfection efficiency. Combination of PEI with PEG or polylysine (PL) reduces cytotoxicity.

[0015] An alternative represents chitosan particles (EP2397123), but these require an acidic pH for preparation, which degrades oligonucleotide drugs and therefore results in low transfection efficiency.

[0016] Polyamidoamine (PMAM)-based dendrimers have also been proposed as biodegradable hyperbranched polymers with high transfection efficiency and capable of encapsulating hydrophilic and hydrophobic drugs. The main limitation concerns their potential cytotoxic effects (Mater.Today,2015,Vol.18,565-572). Polymeric micelles consisting of polymers with hydrophilic and hydrophobic blocks have also been reported, allowing the encapsulation of drugs with different surface wettability.

[0017] Furthermore, hybrid polymer nanoparticles have been described that contain a hydrophobic polymer component, such as poly(lactic-co-glycolic acid), poly(lactic acid), or polycaprolactone, which typically forms the core of the nanoparticle, and a cationic polymer component or lipid component, which constitutes the outer shell of the nanoparticle. They are produced by a nanoprecipitation process, whereby a cationic component complexed with an oligonucleotide drug is deposited on the particle surface. It is also possible to coencapsulate a hydrophobic drug in the core of the hybrid particle. Once exposed to the surface, the oligonucleotide is released immediately. Furthermore, the arrangement of the components makes surface functionalization of nanoparticles for precision medicine difficult.

[0018] Synthetic polymer-cationic moiety hybrid nanoparticles (US9549901) capable of encapsulating oligonucleotides and other hydrophobic drugs have also been prepared by a double emulsion process (water-in-oil-in-water). In this case, the cationic moiety complexed with the oligonucleotide drug forms the core of the nanoparticle, and the synthetic polymer is exposed at the surface of the nanoparticle. Surface functionalization of these nanoparticles can be achieved using various strategies.

[0019] However, the preparation method of nanoparticles consists of two emulsification steps, which is laborious and time-consuming. In addition, surfactants with limited biocompatibility are used, which requires multiple washing steps and finally, large volumes. Overall, the industrial application of the double emulsion process for the preparation of hybrid polymer nanoparticles is complicated.

[0020] US8193334 describes the preparation of hybrid polymer nanoparticles in two steps: first, reverse micelles based on amphiphilic (e.g., lipidic) components containing nucleic acids are prepared in a water-miscible organic solvent (e.g., tetrahydrofuran, THF). Then, a synthetic polymer is solubilized in this solvent. Dropping this solution into water results in a nanoprecipitate of a mixture of synthetic polymer and reverse micelles containing nucleic acids. In particular, the encapsulation efficiency of siRNA is reported to be 18-30%. For the surface functionalization of such nanoparticles, the use of functionalized amphiphilic (e.g., lipidic) and polymeric components is described, since both may be exposed on the nanoparticle surface.

[0021] US2021 / 330597A1 describes polymeric nanoparticles prepared by a double emulsion process, which contain one or more nanocomplexes of lipid-conjugated cationic polymers and nucleic acids, and a polymer shell based on polylactic acid-co-glycolic acid-polyethylene glycol (PLGA-PEG). The weight percentage of the cationic polymer, calculated relative to the amount of cationic polymer and PLGA-PEG, is 20%-55%. The nanoparticle preparation method requires an emulsifier such as polyvinyl alcohol and takes 3 hours to complete the evaporation of the solvent, followed by two final steps of washing / filtration, each for 50 minutes.

[0022] Jinjun Shi et al. (Angewandte Chemie, Vol. 123, n. 31, 7165-7169) describe nanoparticles consisting of three layers (lipid-polymer-lipid) prepared by a double emulsion process and a solvent evaporation process. Specifically, the outer lipids are 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy(polyethylene glycol) (DSPE-PEG) and lecithin, the polymer is PLGA, and finally, the inner lipid is ethyl phosphate choline (EPC) 14:1. The siRNA encapsulation efficiency of the nanoparticles is 78-82%.

[0023] WO2010 / 142660A2 describes microparticles based on a hydrophobic biodegradable polymer (preferably PLGA) and coated with cationic lipids complexed with siRNA, and a method for obtaining the same. The microparticles have a size comprised between 500 nm and 20 μm (preferably between 2 and 20 μm) and are prepared by a W / O / W (water in oil in water) double emulsion process, with an emulsifier being used in the second emulsion (oil in water type). Furthermore, the most abundant component is the cationic lipid, and in fact, the mass ratio of polymer: siRNA: cationic lipid is 5: 25: 50.

[0024] The main methods for the preparation of polymeric nanoparticles capable of releasing oligonucleotides are described in a review published in J. Control. Release, 2019, Vol. 313, 80-95, which also describes inorganic biocompatible nanoparticles with controllable size and morphology based on inorganic materials such as gold, calcium phosphate, silica, and iron oxide.

[0025] Iron oxide (Fe3O4)-based nanoparticles (NPs) are commonly used as contrast agents for magnetic resonance imaging (MRI), and in combination with cationic moieties allow the encapsulation of oligonucleotide drugs.

[0026] Silica NPs and mesoporous silica (MSP) NPs are silica-based nanostructures with high biocompatibility and stability. They can encapsulate oligonucleotide drugs and other drugs and can be surface functionalized with specific molecules for targeted delivery to cells.

[0027] Gold nanoparticles (Au NPs) have been used for drug release due to their biocompatibility, ease of functionalization, and the fact that they can be obtained in desired sizes and shapes. The surface of Au-NPs is usually functionalized with thiol or amine groups to enable the incorporation of oligonucleotide drugs.

[0028] Calcium phosphate nanoparticles (CaP NPs), which have been used for about 40 years to encapsulate and deliver oligonucleotides, are inexpensive, non-toxic, bioabsorbable, and easily synthesizable. Disadvantages of such nanoparticles include low encapsulation efficiency (10-20%) and the difficulty of coencapsulating other types of drugs.

[0029] The main drawback of some inorganic nanoparticles is that they are non-degradable and can accumulate in the body, resulting in potential long-term side effects.A common limitation of all inorganic nanoparticles is their limited encapsulation efficiency.

[0030] The use of viral vectors derived from, for example, retroviruses, lentiviruses, adenoviruses, herpes viruses, etc. for the delivery of oligo- or polynucleotides offers advantages such as cell transfection efficiency, but involves safety issues for patients due to the risk of inflammatory reactions and carcinogenicity (in the case of integrative viral vectors). Furthermore, although viral vectors can show high selectivity for some cells, targeted action cannot be expected. [Prior art documents] [Patent documents]

[0031] [Patent Document 1] U.S. Patent No. 10,555,910 [Patent Document 2] European Patent Application Publication No. 2397123 [Patent Document 3] U.S. Patent No. 9,549,901 [Patent Document 4] U.S. Patent No. 8,193,334 [Patent Document 5] US Patent Application Publication No. 2021 / 330597 [Patent Document 6] International Publication No. 2010 / 142660 Summary of the Invention

[0032] Description of the Invention It has been demonstrated that drug-releasing hybrid polymer nanoparticles capable of efficiently encapsulating oligonucleotides (alone or in combination with hydrophobic drugs) can be obtained by a rapid, simple, efficient and scalable process, ensuring controlled and sustained delivery of oligonucleotide drugs.

[0033] The hybrid polymer nanoparticles according to the invention are biocompatible and can be easily functionalized on their surface by a rapid, simple and versatile process, thereby addressing various needs of precision medicine. By utilizing specific surface functionalization, the nanoparticles according to the invention protect the encapsulated drug from degradation and allow its efficient delivery to the target cells.

[0034] According to the present invention, these and other advantages are achieved by hybrid nanoparticles consisting of a polymer component encapsulating cationic liposomes and / or lipoplexes containing cationic lipids and helper lipids, in which the polymer phase represents at least 80% by weight of the total nanoparticle material.

[0035] The nanoparticles of the present invention can be prepared via a nanoprecipitation process of a polymer solution (which may also contain the hydrophobic drug) in an aqueous dispersion of liposomes and / or lipoplexes encapsulating oligonucleotide drugs and / or hydrophobic drugs, resulting in an exposed polymer phase at the surface.

[0036] This effectively protects the oligonucleotide drug from degradation and allows its sustained and controlled delivery over long periods of time.Furthermore, the presence of synthetic polymers on the surface of the nanoparticles allows for efficient and versatile functionalization, conferring stability during storage.

[0037] The nanoparticles can be stored in aqueous suspension at a temperature of 4° C. for at least one month without the aid of a stabilizing agent. Alternatively, the nanoparticles can be frozen and thawed for use in aqueous suspension to restore their properties by adding a suitable cryoprotectant. The nanoparticles can also be frozen and lyophilized, and the suspension can be reconstituted prior to use by adding a cryoprotectant, preserving the physicochemical and functional properties.

[0038] Furthermore, nanoparticles have an in vivo stability ranging from days to weeks, depending on their chemical composition, allowing a controlled, sustained and complete release of the encapsulated active ingredient.

[0039] The preparation of nanoparticles involves nanoprecipitation of a polymer solution into a dispersion of cationic liposomes or lipoplexes (containing cationic lipids and helper lipids), typically by adding a polymer solution in a water-miscible organic solvent dropwise to an aqueous dispersion of liposomes or lipoplexes under stirring. The water-miscible organic solvent is evaporated in a rotary vacuum evaporator. Examples of water-miscible organic solvents include alcohols, ketones, acetonitrile, dimethyl sulfoxide, preferably acetone.

[0040] Nanoprecipitation can be advantageously carried out in a microfluidic device.

[0041] The preparation does not require potentially toxic additives, surfactants, or emulsifiers, and the manufacturing process is efficient, with yields of more than 95% (typically 97%), calculated as the percentage by weight of product (nanoparticles) relative to the weight of materials used. The amount of solvent required for the preparation is limited, favoring the scalability of the process. The time required for the preparation of hybrid nanoparticles is on average less than one hour.

[0042] Hybrid polymer nanoparticles based on synthetic polymer and lipid components combine the biomimicry of lipid components with the stability and versatility of synthetic polymers. The hybrid nanoparticles of the subject of the present invention are a new platform for precision medicine, since they can efficiently encapsulate oligonucleotides (by cationic lipid components) and possibly in combination with hydrophobic or weakly hydrophilic drugs (by polymer components) and deliver them to target cells using specific surface functionalization. The mild process conditions preserve the functionality of oligonucleotide drugs. The release profile of oligonucleotides and any other co-encapsulated drugs is more controlled and sustained than lipid nanoparticles.

[0043] Thus, hybrid nanoparticles reduce the systemic toxicity of therapeutic agents, improve their release, and require smaller doses than, for example, lipid nanoparticles. Furthermore, their increased stability compared to lipid nanoparticles allows them to be stored in suspension at a temperature of 4° C. for at least 30 days without altering their physicochemical properties (including encapsulation efficiency).

[0044] The versatility of this process promises a wide range of applications to meet various therapeutic needs, such as tumor treatment, regenerative cardiovascular, liver, and renal medicine, treatment of neuromuscular diseases, and mRNA vaccines.

[0045] The nanoparticles according to the invention differ from those described in US8193334 both in that they have a higher encapsulation efficiency of oligonucleotides (in the range of 96-100%, higher than the 18-30% reported in US8193334) and in that they are able to encapsulate not only oligonucleotide drugs but also hydrophobic or moderately hydrophilic compounds. Moreover, the preparation process is completely different: according to the invention, nanoprecipitation of a solution of a synthetic polymer takes place on a dispersion containing preformed lipoplexes, allowing the synthetic polymer to cover them. Thus, the method according to the invention allows to obtain particles with the synthetic polymer exposed to the outside faster (one step less) and more efficiently. [Brief description of the drawings]

[0046] [Figure 1] DLS analysis of PLGA / DE-DOPE / NegmiR and DE-DOPE / NegmiR nanoparticles in Milli-Q water. [Diagram 2] Cryo-electron microscopy (CryoTEM) analysis of PLGA / DE-DOPE / NegmiR nanoparticles. [Diagram 3] Encapsulation efficiency of miRNA in PLGA / DE-DOPE / NegmiR and DE-DOPE / NegmiR nanoparticles. [Figure 4] Storage stability of PLGA / DE-DOPE / NegmiR nanoparticles in Milli-Q water at 4 °C evaluated by DLS analysis. [Diagram 5] Storage stability of PLGA / DE-DOPE / NegmiR nanoparticles at 4 °C in Milli-Q water and PBS (phosphate buffered saline) evaluated by DLS analysis. [Figure 6] Storage stability of PLGA / DE-DOPE / NegmiR nanoparticles in Milli-Q water and DMEM+FBS at 4 °C assessed by DLS analysis. [Figure 7] Release of miRNA (NegmiR) from PLGA / DE-DOPE / NegmiR nanoparticles at dynamic conditions in Milli-Q water at 37 °C, assessed by Qubit fluorescence analysis. [Figure 8] Cytofluorescence analysis of adult human atrial cardiac fibroblasts (AHCF, control) and AHCF treated with PLGA-Cy5 based hybrid polymer nanoparticles. Left panels report cell fluorescence (y-axis) versus cell forward scatter (x-axis). Right panels report cell fluorescence (x-axis) versus cell number (y-axis). [Figure 9] The image on the left shows intracellular miR-1 expression after cell transfection with PLGA / DE-DOPE / miRNA nanoparticles 48 hours after transfection, relative to the control (non-transfected AHCF). The image on the right shows the expression of the target of miR-1 (Twf-1) 48 hours after transfection, relative to the control (non-transfected AHCF). [Figure 10] Hydrodynamic diameter, zeta potential, and encapsulation efficiency of PLGA / DE-DOPE / miRNA nanoparticles loaded with NegmiR and miRcombo. DLS analysis was performed in Milli-Q water. [Figure 11] Stability of PLGA / DE-DOPE / miRcombo nanoparticles in DMEM-FBS medium evaluated by DLS analysis. [Figure 12] Stability of PLGA / DE-DOPE / miRcombo nanoparticles in Milli-Q water at 4 °C assessed by DLS analysis. [Figure 13] In vitro release of miRcombo in Milli-Q water and PBS under dynamic conditions at 37°C. [Figure 14]Cell viability by resazurin assay performed 24, 48, and 72 hours after transfection for AHCF treated with PLGA / DE-DOPE / miRNA nanoparticles (containing negmiR or miRcombo). Cells (5.5×103) were treated with PLGA / DE-DOPE / miRNA nanoparticles (containing negmiR or miRcombo, final 25 nM). Values ​​are reported relative to control (non-transfected AHCF cells). [Figure 15] Live / Dead assay performed 72 hours after transfection on AHCFs treated with PLGA / DE-DOPE / miRNA nanoparticles (containing negmiR or miRcombo). Cells (5.5 × 103) were treated with PLGA / DE-DOPE / miRNA nanoparticles (containing negmiR or miRcombo, final concentration 25 nM). [Figure 16] Expression of single microRNAs (miR-1, miR-133, miR-208, miR-499) in AHCFs treated with PLGA / DE-DOPE / miRNA nanoparticles (containing negmiR or miRcombo) was assessed by droplet digital PCR 48 hours after transfection. Expression levels of single microRNAs are reported as fold change relative to negmiR control. [Figure 17] Direct cardiac regeneration efficiency in miRcombo-treated AHCFs using DharmaFECT® / miRNA and PLGA / DE-DOPE / miRNA, as assessed by droplet digital PCR for TNNT2 expression 15 days after transfection. TNNT2 expression levels are related to GAPDH expression (used as a housekeeping internal gene). [Figure 18] Hydrodynamic diameter and zeta potential of negmiR-loaded PLGA / DE-DOPE / miRNA and PLGA-PEG / PLGA / DE-DOPE / miRNA nanoparticles. DLS analysis was performed in Milli-Q water. [Figure 19] Hydrodynamic diameter and zeta potential of PLGA-PEG / PLGA / DE-DOPE / negmiR and IgG / PLGA-PEG / PLGA / DE-DOPE / negmiR nanoparticles. DLS analysis was performed in Milli-Q water. [Figure 20] Fourier infrared spectroscopy (FTIR) of PLGA / DE-DOPE / negmiR nanoparticles (a), PLGA-PEG powder (b) (both used as controls), PLGA-PEG / PLGA / DE-DOPE / negmiR nanoparticles (c), and IgG / PLGA-PEG / PLGA / DE-DOPE / negmiR nanoparticles (d). [Figure 21] Cell viability and cytotoxicity assessed 24 hours after transfection for AHCFs treated with PLGA-PEG / PLGA / DE-DOPE / negmiR and IgG / PLGA-PEG / PLGA / DE-DOPE / negmiR nanoparticles. Cells (5.5 × 103) were treated with different concentrations (corresponding to 25, 18.75, 12.5, and 6.25 nM miRNA) of PLGA-PEG / PLGA / DE-DOPE / negmiR and IgG / PLGA-PEG / PLGA / DE-DOPE / negmiR nanoparticles. Values ​​are reported relative to control (non-transfected AHCFs). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0047] Detailed Description of the Invention The polymer component used in the preparation of the nanoparticles of the present invention may be a single polymer or a mixture of polymers.

[0048] The polymer component is selected from the following: (i) polyesters, such as poly(lactic-co-glycolic acid) (polylactic-co-glycolic acid, PLGA), poly(glycolic acid) (PGA), poly(lactic acid) (PLA), polycaprolactone (PCL), poly(lactide-co-caprolactone) (PLCL); (ii) polyesters from the poly(hydroxyalkanoates) family, such as poly(hydroxybutyrate) (PHB) and the copolymer poly(hydroxybutyrate-co-hydroxyvalerate) (PHBHV); (iii) poly(propylene oxide) (PPO); (iv) polymers and copolymers containing methacrylate groups, such as poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), and poly(butyl methacrylate) (PBMA); (v) poly(cyanoacrylate); (vi) polymers (i) and / or (ii) and / or (iii) and / or (iv) and / or (v), copolymers comprising poly(ethylene glycol) PEG and / or (polyethylene oxide) PEO as building blocks; (vii) polyurethanes or other synthetic polymers (containing the above polymers as building blocks); (viii) natural polymers such as zein, cellulose, lignin, and starch; (ix) Natural polymers modified to make them water-insoluble (e.g., butyl glyceryl pectin).

[0049] The copolymer poly(lactic-co-glycolic acid) is widely used due to its biocompatibility and biodegradability.

[0050] Cationic lipids include a hydrophilic head group that carries a permanent positive charge, for example a hydrophilic head group that includes an ammonium group.

[0051] Examples of cationic lipids include cationic cholesterol derivatives such as [2-(2,3-didodecyloxypropyl)-hydroxyethyl]ammonium bromide (DE), 1,2-di-O-octadecenyl-3-trimethylammonium propane (DOTMA), 1,2-dioleoyloxy-3-[trimethylammonium]-propane (DOTAP), dimethyl-dioctadecylammonium bromide (DDAB), cetyl-trimethylammonium bromide (CTAB); bis-guanidinium-tren-cholesterol (BGTC), 2,3-dioleyloxy-N-[2-(sperminecarboxamido)ethyl]-N,N-dimethyl-1-propaneaminotrifluoroacetate (DOSPA).

[0052] The weight ratio of the lipids (cationic lipid and helper lipid) to the entire nanoparticles can be in the range of 1 to 20%.

[0053] The helper lipid is composed of one or more phospholipids selected from phosphatidylethanolamine, phosphatidylcholine, cholesterol, and derivatives thereof. The weight ratio of the helper lipid to the cationic lipid can be in the range of 1-50%. The weight ratio of the cationic lipid to the helper lipid is preferably 50:50.

[0054] The size of the nanoparticles can be in the range of 80 to 500 nm. A preferred embodiment of the present invention comprises nanoparticles containing lipoplexes including a polynucleotide selected from microRNA, siRNA, messenger RNA, plasmid DNA, and antisense oligonucleotides.

[0055] The encapsulation efficiency of polynucleotides is 96-100%. The hybrid nanoparticle system of the present invention can release 100% of the loaded active agent, especially RNA, for 7-9 days. The system is stable for at least one month under storage conditions at 4°C.

[0056] Alternatively, or in addition to polynucleotides, the nanoparticles can also carry hydrophobic or slightly hydrophilic drugs dispersed in cationic liposomes or polymers.

[0057] In the nanoparticles of the present invention, the polymer can be surface functionalized with one or more ligands, such as antibodies, antigen-binding antibody fragments (Fabs), aptamers, peptides, carbohydrates, small molecules, or combinations of the above.

[0058] The invention is explained in more detail in the following examples and the accompanying drawings. EXAMPLES

[0059] [Example 1: Preparation of nanoparticles] We used PLGA polymer, [2-(2,3-didodecyloxypropyl)-hydroxyethyl]ammonium bromide (DE) cationic lipid, and L-α-dioleoylphosphatidylethanolamine (DOPE) helper lipid, however, this method is applicable to any other type of polymer or other lipid combination while keeping the polymer content above 80 wt%.

[0060] PLGA is dissolved in acetone (1 mg / mL). A volume of 1 mL of DE-DOPE / miRNA lipoplexes is poured into a glass test tube and stirred (approximately 900-1000 rpm).

[0061] Then, the starting PLGA solution diluted to a concentration of 127 μg / mL was added dropwise to the lipoplex suspension under magnetic stirring, and the system was left under stirring for 30 min. The acetone was then removed by evaporation. By this method, a volume of 1 mL of PLGA / DE-DOPE / miRNA nanoparticles was obtained. First, NegmiR and miR-1 were encapsulated as miRNA. Then, four miRNAs (miRcombo: miR-1, 133, 208, 499) were encapsulated simultaneously. Using the same method, siRNA can also be encapsulated, with similar size, zeta potential, and encapsulation efficiency as miRNA. For larger oligonucleotides, such as mRNA, the N / P ratio between lipid amine groups and mRNA phosphate groups needs to be optimized.

[0062] The PLGA / DE-DOPE / miRNA nanoparticles are functionalized on their surface with ligands (antibodies, antibody fragments, peptides, or aptamers) specific for adult human cardiac fibroblasts. The functionalization is carried out by click chemistry, specifically, copper-catalyzed Cu(I) Huisgen azide-alkyne cycloaddition. This functionalization reaction involves the following four steps: 1) Functionalization of PLGA polymer by reaction of azide-bearing modified PEG (PEG-N3) with carbodiimide to obtain PLGA-PEG-N3 (or use of commercially available PLGA-PEG-N3 copolymer); 2) Preparation of PLGA-PEG-N3 / DE-DOPE / miRNA nanoparticles by nanoprecipitation; 3) Functionalization of the ligand with propargyl-PEG-NHS (NHS: N-hydroxybutyric acid imide) to obtain the molecule propargyl-PEG-ligand; 4) Conjugation of propargyl-PEG-ligands bearing alkyne groups to the azide groups exposed by PLGA-PEG-N3 / DE-DOPE / miRNA nanoparticles.

[0063] This type of functionalization can also be applied to other therapeutic purposes by varying the type of ligand.

[0064] [Example 2: Characterization of nanoparticles] a) Hydrodynamic size and zeta potential (Z-potential) The hydrodynamic size of the hybrid PLGA / DE-DOPE / miRNA nanoparticles in Milli-Q water is 153 nm, which is significantly smaller than that of the control DE-DOPE / NegmiR lipoplexes (372 nm). The zeta potential of the PLGA / DE-DOPE / miRNA nanoparticles is negative at -28 mV due to the presence of PLGA on the surface. The DE-DOPE / NegmiR lipoplexes have a positive zeta potential (40 mV) (Figure 1).

[0065] DLS analysis of PLGA / DE-DOPE / miRNA nanoparticles in various media showed similar results as reported in Table 1. This indicates the stability of the nanoparticles when in contact with various media.

[0066] Table 1: DLS analysis of PLGA / DE-DOPE / NegmiR nanoparticles in various suspension media (PBS: phosphate-buffered saline; Dulbecco's modified Eagle's medium (DMEM) + fetal bovine serum (FBS): medium containing fetal bovine serum).

[0067] [Table 1]

[0068] b) Morphological analysis of nanoparticles Cryo-EM images (Figure 2) show regions of different densities, suggesting that PLGA has precipitated over the lipoplexes: the size is nanometers, the particles are separated from each other, and do not form aggregates.

[0069] c) Encapsulation efficiency of oligonucleotides (miRNA), EE% The encapsulation efficiency of the model miRNA (NegmiR) in the PLGA / DE-DOPE / NegmiR nanoparticles and DE-DOPE / NegmiR lipoplexes was 99% (Figure 3). These data were obtained by analyzing the supernatant after the nanoprecipitation process using Qubit fluorescence technology.

[0070] d) Preparation yield of hybrid nanoparticles The yield of the manufacturing process (calculated as the weight of nanoparticles produced relative to the weight of materials used in the process) was 97 ± 1% for PLGA / DE-DOPE / NegmiR hybrid polymer nanoparticles.

[0071] e) Storage stability of suspension in Milli-Q water at 4°C The hydrodynamic diameter and zeta potential are stable for at least 28 days of culture in suspension in Milli-Q water at 4°C (Figure 4).

[0072] f) Storage stability in Milli-Q water and PBS at 37°C for up to 48 hours In the stability study performed at 37 °C for 48 h, PLGA / DE-DOPE / miRNA nanoparticles in Milli-Q water showed good colloidal stability, whereas incubation in PBS led to a slight, albeit non-significant, increase in size and PDI after 48 h (Figure 5). The zeta potential remained constant at a negative value (-23 mV) in Milli-Q water, whereas the presence of PBS led to a slight decrease in the zeta potential (-32 mV) at 48 h (Figure 5). Therefore, in this case, it was assumed that the interaction between the ions present in the solution and the nanoparticles influenced the size after 48 h. Moreover, the standard deviation (DS) values ​​suggest that the interaction with ions by the PLGA / DE-DOPE / miRNA nanoparticle suspension in PBS may have affected the reproducibility of the DLS analysis.

[0073] g) Storage stability in Milli-Q water and DMEM+FBS at 37°C for up to 48 hours Finally, the average size and zeta potential of PLGA / DE-DOPE / miRNA nanoparticles observed after 48 h of incubation in cell culture medium (DMEM+FBS) changed slightly compared to when incubated in Milli-Q water (Figure 6). The initial average hydrodynamic size of PLGA / DE-DOPE / miRNA nanoparticles in DMEM+FBS was 172 nm, which increased to 260 nm after 48 h of incubation. The zeta potential value of nanoparticles in DMEM+FBS increased to -10 mV and remained stable throughout the test period (Figure 6). Such changes could be the result of the interaction of the NP surface with serum proteins. However, the PDI values ​​(0.25–0.26) measured after 48 h of incubation also indicate that PLGA / DE-DOPE / miRNA nanoparticles maintain good colloidal stability in DMEM+FBS.

[0074] The PLGA / DE-DOPE / negmiR nanoparticles in static conditions do not release miRNA in Milli-Q water at 37 °C, indicating that the oligonucleotide drug is protected. Instead, in dynamic conditions at 37 °C, the PLGA / DE-DOPE / negmiR nanoparticles show a stepwise delivery that reaches a release value of 73% after 24 h and is completely released after 7 days (Figure 7). In contrast, the DE-DOPE / negmiR particles show a complete release within 24 h under static conditions (data not shown). The profile obtained in Figure 7 reflects the well-known properties of PLGA as a material that can protect drugs from degradation and ensure controlled release kinetics.

[0075] h) In vitro efficacy assessment: uptake, cytotoxicity, miRNA-1 expression, and target downregulation (Twf1) miRNA is efficiently delivered into cells as shown by cell tests (using adult human atrial cardiac fibroblasts AHCF) through the evaluation of the cellular uptake efficiency (cytofluorescence analysis) of fluorescent hybrid polymer nanoparticles containing PLGA labeled with Cyanine-5. 24 hours after the start of the transfection treatment, 99% of the cells were found to be Cyanine-5 positive, highlighting the internalization effect of the nanoparticles by the cells (Figure 8).

[0076] Further cell testing was performed by transfecting AHCF with hybrid polymer nanoparticles loaded with miR-1 or control negmiR for 24 h. For performance comparison, the same cells were transfected with DE-DOPE / miRNA lipid particles. As assessed by Droplet Digital PCR (ddPCR), miR-1 expression was significantly increased with the two types of nanoparticles loaded with miR-1 (lipid or hybrid) compared to the control (Figure 9: left image). Also, Twf1 downregulation was similar in the two experimental examples of cell transfection with lipid or hybrid particles releasing miR-1 (Figure 9: right image).

[0077] i) Encapsulation of miRcombo: Hydrodynamic size and zeta potential Four miRNAs (miRcombo) were encapsulated into hybrid nanoparticles to evaluate their physicochemical properties. As shown in the data in Table 2, encapsulation of miRcombo does not change the hydrodynamic size, zeta potential, PDI, and encapsulation efficiency of the nanoparticles compared to encapsulation of a single miRNA.

[0078] Table 2: Characteristics of PLGA / DE-DOPE / miRcombo nanoparticles evaluated by DLS analysis.

[0079] [Table 2]

[0080] In Figure 10, the properties of hybrid particles loaded with a single miRNA (NegmiR) are compared with those of hybrid nanoparticles encapsulating miRcombo (four miRNAs, total dosage equal to the NegmiR content of the other particles), clearly showing the same hydrodynamic size, zeta potential, and PDI properties.

[0081] j) DLS analysis of PLGA / DE-DOPE / miRcombo nanoparticles cultured in DMEM+FBS The stability of the PLGA / DE-DOPE / miRcombo nanoparticles in culture medium (DMEM+FBS) is similar to that of the PLGA / DE-DOPE / negmiR nanoparticles (Figure 11). After 48 h of incubation, a slight change in the average size of the PLGA / DE-DOPE / miRcombo nanoparticles was observed. The initial average hydrodynamic size of the PLGA / DE-DOPE / miRcombo nanoparticles in DMEM+FBS was 167 nm, which increased to 275 nm after 48 h of incubation. Moreover, after 7 days, a further increase in the hydrodynamic diameter (410 nm) was measured, possibly due to the generation of a protein corona. The zeta potential of the nanoparticles in DMEM+FBS was -10 mV (i.e., higher than the value in Milli-Q water) and remained stable throughout the test period. This change could be the result of the interaction of the NP surface with serum proteins. Finally, the PDI values ​​after 48 h of culture were stable, indicating that the PLGA / DE-DOPE / miRcombo nanoparticles maintained good colloidal stability in DMEM+FBS during the transfection period (24 h) and allowed in vitro transfection for up to 48 h.

[0082] k) Stability of hybrid polymer nanoparticles containing miRcombo under storage conditions (4°C, Milli-Q water) The hydrodynamic diameter and zeta potential of PLGA / DE-DOPE / miRcombo nanoparticles were stable when incubated in Milli-Q water at 4 °C for up to 28 days (Figure 12 ).

[0083] In vitro release of miRcombo under dynamic conditions in milli-Q water at 37°C is complete in 168 hours (7 days), similar to the release of NegmiR (Figure 7, Figure 13). The release after 24 hours is about 7%, which slowly increases until 7 days.

[0084] Instead, in physiological conditions (PBS), the release was more gradual, reaching 90% after 192 h (8 days), presumably because surface adsorption of cations from PBS contributes to slowing the release of miRNAs (which are negatively charged).

[0085] l) Biocompatibility Nanoparticles loaded with miRcombo or negmiR are also biocompatible with AHCF, as shown by resazurin assays performed up to 72 h from the start of transfection (Figure 14).

[0086] Live / Dead assays performed on AHCFs after 24 h of transfection with nanoparticles carrying negmiR or miRcombo (at the same doses used in the biocompatibility studies) and subsequent cell culture for up to 72 h showed a cell viability of 95% (Figure 15).

[0087] Furthermore, the miRcombo is efficiently released into cells, as demonstrated by cellular studies evaluating the presence of single microRNAs by ddPCR analysis 48 hours after transfection (Figure 16).

[0088] Evaluation of the expression of the cardiac marker TNNT2 (by ddPCR analysis) on day 15 of culture demonstrated the efficacy of administration of miRcombo with hybrid PLGA / DE-DOPE / miRNA nanoparticles, as it highlighted the trans-differentiation of cells mediated by miRcombo, which was higher than that of the commercially available transfectant DharmaFECT (Figure 17).

[0089] m) PLGA / PLGA-PEG / DE-DOPE / miRNA nanoparticles: hydrodynamic size and zeta potential Hybrid nanoparticles containing negmiR were also prepared using a polymer mixture of PLGA and PLGA-PEG with a weight ratio of the components of 50:50 instead of PLGA alone. As can be seen from the data reported in Table 3, the resulting nanoparticles showed no changes in hydrodynamic size, zeta potential, PDI, and encapsulation efficiency compared to PLGA / DE-DOPE / negmiR nanoparticles.

[0090] Table 3: Characteristics of PLGA-PEG / PLGA / DE-DOPE / miRNA nanoparticles evaluated by DLS analysis.

[0091] [Table 3]

[0092] In Figure 18, the properties of the hybrid PLGA / DE-DOPE / miRNA particles are compared with the PLGA-PEG / PLGA / DE-DOPE / miRNA hybrid nanoparticles, clearly showing similar properties in hydrodynamic diameter, zeta potential, and PDI.

[0093] n) Surface functionalization with model molecules (immunoglobulin G-IgG) as ligands: hydrodynamic size and zeta potential The hybrid nanoparticles were functionalized with IgG as a model ligand molecule (IgG / PLGA-PEG / PLGA / DE-DOPE / miRNA). The PLGA-PEG copolymer used has a terminal azide group that is used for conjugation. The IgG molecules were pre-modified to expose alkyne groups. The PLGA-PEG / PLGA / DE-DOPE / miRNA nanoparticles were incubated in a solution containing the IgG modified molecules in the presence of copper as a catalyst.

[0094] The functionalized hybrid nanoparticles were characterized in terms of hydrodynamic size, PDI, and zeta potential by DLS analysis. As shown in Figure 19, the hybrid IgG / PLGA-PEG / PLGA / DE-DOPE / miRNA nanoparticles showed an increase in hydrodynamic diameter (494 ± 29 nm) and zeta potential (-3 ± 0.03 mV) associated with the presence of IgG on the surface.

[0095] As shown in FIG. 20, in the FTIR-ATR spectrum of the IgG / PLGA-PEG / PLGA / DE-DOPE / miRNA nanoparticles, -1 and 3100 cm -1 The absorption bands due to CH stretching of methylene groups (mainly attributed to PEG) and C=O stretching of ester groups of polyester, as well as the absorption band of azide groups, present in the FTIR-ATR spectrum of PLGA-PEG / PLGA / DE-DOPE / miRNA nanoparticles, are significantly attenuated in the spectrum of nanoparticles functionalized with IgG, confirming the presence of IgG on the NP surface.

[0096] o) In vitro assays: viability and cytotoxicity of PLGA-PEG / PLGA / DE-DOPE / negmiR and IgG / PLGA-PEG / PLGA / DE-DOPE / negmiR nanoparticles Cytocompatibility studies were performed by transfecting AHCFs with PLGA-PEG / PLGA / DE_DOPE / negmiR and IgG / PLGA-PEG / PLGA / DE-DOPE / negmiR polymeric nanoparticles at different concentrations (25, 18.75, 12.5, and 6.25 nM miRNA) for 24 h. Both nanoparticle formulations showed high cell viability and low cytotoxicity (Figure 21), confirming the cytocompatibility of the nanoparticles.

[0097] p) PLA / DE-DOPE / miRNA nanoparticles: hydrodynamic size and zeta potential Hybrid nanoparticles were also prepared using other polymers, specifically PLA, and as shown by the data reported in Table 4, the resulting nanoparticles showed no changes in hydrodynamic size, zeta potential, PDI, and encapsulation efficiency relative to PLGA / DE-DOPE / negmiR nanoparticles.

[0098] Table 4: Characteristics of PLA / DE-DOPE / miRNA nanoparticles evaluated by DLS analysis.

[0099] [Table 4]

[0100] q) Zein / DE-DOPE / miRNA nanoparticles: hydrodynamic size and zeta potential Hybrid nanoparticles were also prepared using other polymers, specifically zein, and the resulting nanoparticles showed no changes in hydrodynamic size, zeta potential, PDI, and encapsulation efficiency relative to PLGA / DE-DOPE / negmiR nanoparticles, as shown by the data reported in Table 5.

[0101] Table 5: Characteristics of zein / DE-DOPE / miRNA nanoparticles evaluated by DLS analysis.

[0102] [Table 5]

Claims

1. A hybrid nanoparticle comprising a polymer component encapsulating a lipid core containing cationic liposomes or lipoplexes comprising cationic lipids and helper lipids, said polymer component accounting for at least 80% by weight of the total material constituting said nanoparticle, said hybrid nanoparticle being obtained by nanoprecipitation of a solution of said polymer component in a dispersion of said cationic liposomes or lipoplexes.

2. The nanoparticle of claim 1 , wherein the polymer component is a single polymer or a mixture of polymers.

3. 3. The nanoparticles according to claim 1 or 2, wherein the polymer component is selected from polyesters, poly(hydroxyalkanoates), poly(propylene oxide), methacrylic polymers or copolymers, poly(cyanoacrylates), polyurethanes, their copolymers with PEG and / or poly(ethylene oxide), optionally modified natural polymers.

4. 4. The nanoparticles of claims 2 and 3, wherein the polymer component is selected from poly(lactic acid-co-glycolic acid), poly(glycolic acid), poly(lactic acid), polycaprolactone, poly(lactide-co-caprolactone), poly(hydroxybutyrate), copolymers poly(hydroxybutyrate-co-hydroxyvalerate), poly(propylene oxide), poly(methyl methacrylate), poly(ethyl methacrylate), poly(butyl methacrylate), zein, cellulose, lignin, starch, butyl glyceryl pectin.

5. The nanoparticle of any one of claims 1 to 4, wherein the cationic lipid comprises a hydrophilic head group carrying an ammonium group and a permanent positive charge.

6. 6. The nanoparticle of claim 5, wherein the lipid core comprises a cationic lipid selected from [2-(2,3-didodecyloxypropyl)-hydroxyethyl]ammonium bromide, 1,2-di-O-octadecenyl-3-trimethylammonium propane, 1,2-dioleyloxy-3-[trimethylammonium]-propane, dimethyl-dioctadecylammonium bromide, cetyl-trimethylammonium bromide, 2,3-dioleyloxy-N-[2-(sperminecarboxamido)ethyl]-N,N-dimethyl-1-propaneaminotrifluoroacetate, bis-guanidinium-tren-cholesterol.

7. The nanoparticles according to one or more of claims 1 to 6, wherein the helper lipid is selected from phosphatidylethanolamine, phosphatidylcholine, cholesterol, or mixtures thereof.

8. The nanoparticle according to claim 1 , wherein the lipoplex comprises a polynucleotide selected from microRNA, siRNA, mRNA, plasmid DNA, and antisense oligonucleotides.

9. The nanoparticles according to one or more of claims 1 to 8, wherein the weight ratio of the cationic lipid to the helper lipid is 50:

50.

10. The nanoparticle of claim 1 , further comprising a hydrophobic drug.

11. Nanoparticles according to one or more of the preceding claims, which are functionalized with one or more ligands.

12. The nanoparticle of claim 11 , wherein the ligand is an antibody, an antigen-binding antibody fragment (Fab), an aptamer, a peptide, a carbohydrate, a small molecule, or a combination thereof.

13. A method for preparing nanoparticles according to claims 1 to 12, comprising the steps of: a) preparation of an aqueous dispersion of liposomes or lipoplexes; b) adding dropwise, under stirring, a solution of the polymer component in a water-miscible organic solvent to the aqueous dispersion of liposomes or lipoplexes; c) removing the organic solvent; The method includes:

14. The method of claim 13 , wherein the nanoprecipitation occurs in a microfluidic device.

15. 15. The method of claim 13 or 14, wherein no emulsifiers or surfactants are added.

16. Hybrid nanoparticles according to claims 1 to 12 for use in regenerative medicine, cell reprogramming, treatment of tumors, treatment of neurodegenerative diseases and as vaccines.

Citation Information

Patent Citations

  • Nanoparticles for nucleic acid delivery

    EP2397123A1

  • Oligonucleotide lipid nanoparticle compositions, methods of making and methods of using the same

    US10555910B2

  • Nanoparticle Depot For Controlled And Sustained Gene Delivery

    US20210330597A1

  • Polymer-encapsulated reverse micelles

    US8193334B2

  • Lipid-polymer hybrid particles

    US9549901B2